2001
DOI: 10.1021/jp0033317
|View full text |Cite
|
Sign up to set email alerts
|

Surface Analysis Studies of Yield Enhancements in Secondary Ion Mass Spectrometry by Polyatomic Projectiles

Abstract: In this paper we examine the mechanism of secondary ion yield enhancements previously observed for polyatomic projectiles by measuring the weight loss, volume loss, and surface composition of poly(methyl methacrylate) (PMMA) films sputtered by keV SF 5 + and Ar + projectile ions. The sputter yieldsthe amount of material removed from the surface by 3.0 keV SF 5 + projectilesswas found to be 2.2 ( 0.8 higher than for Ar + projectiles, measured by weight loss in the PMMA film with a quartz crystal microbalance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 25 publications
4
80
2
Order By: Relevance
“…The general features of this profile are quite similar to those reported using SF 5 þ projectiles [1]. To obtain a clearer picture of how the monitored signal intensities vary as a function of depth into the sample, normalized PMMA and Au intensities are plotted in Fig.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The general features of this profile are quite similar to those reported using SF 5 þ projectiles [1]. To obtain a clearer picture of how the monitored signal intensities vary as a function of depth into the sample, normalized PMMA and Au intensities are plotted in Fig.…”
Section: Resultssupporting
confidence: 72%
“…do not yield useful depth information since too much damage is created on the surface to accurately attain molecular specificity in each layer. Fuoco et al [1] have reported that polyatomic primary ion beam sources such as SF 5 þ are much better suited for depth profiling through organic substrates. For equal beam energies, polyatomic projectiles penetrate the surface to much lower depths than their atomic counterparts and offer substantial sputter yield and secondary ion yield enhancements for molecular ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Cluster ion beams have been of interest in these types of experiments for many years since it has been noticed that surface molecules are desorbed with greater efficiency than with corresponding atomic ion beams. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] When C 60 strikes a surface, however, the subsequent energy dissipation processes give rise to several fascinating phenomena with significant scientific implications. Detailed studies are now possible since a stable, long-lived source of C 60 + ions has recently been developed.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a SF 5 + cluster ion as a depth profiling etch tool for use on polymeric samples has been demonstrated by Fuoco et al employing PMMA thin film on silicon [13], Norrman et al also used PMMA and poly(vinyl chloride) films spin coated onto Si wafer [14] and by Mahoney et al who investigated poly(L-lactic acid) (PLLA) doped with 4-acetaminodophenol [15] and PLLA blended with a triblock co-polymer [16]. Most recently, with the introduction of the Buckminsterfullerene (C 60 ) cluster ion source as an etch tool, the depth profiling of polymeric (or organic) materials has taken great strides forward.…”
Section: Introductionmentioning
confidence: 99%